Safety evaluation of an extension of use of the food enzyme β‐amylase from the non‐genetically modified Bacillus flexus strain AE‐BAF - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme β‐amylase (4‐α‐d‐glucan maltohydrolase, EC 3.2.1.2) is produced with the non‐genetically modified Bacillus flexus strain AE‐BAF by Amano Enzyme Inc. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in three food manufacturing processes. Subsequently, the applicant requested to extend its use to four additional processes and revised the use levels. In this assessment, EFSA updated the safety evaluation of this food enzyme for use in a total of seven food manufacturing processes. As the food enzyme‐total organic solids (TOS) are removed from the final foods in one food manufacturing process, the dietary exposure to the food enzyme‐TOS was estimated only for the remaining six processes. The dietary exposure was estimated to be up to 0.247 mg TOS/kg body weight per day in European populations. Based on the data provided for the previous evaluation and the dietary exposure revised in the present evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.